1977
DOI: 10.1128/jcm.5.6.564-569.1977
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of anaerobic, facultative, and aerobic bacteria from clinical specimens in three anaerobic transport systems

Abstract: With aspirated specimens from clinical infections, we evaluated the recovery of anaerobic, aerobic, and facultative bacteria in three widely used transport systems: (i) aspirated fluid in a gassed-out tube (FGT), (ii) swab in modified Cary and Blair transport medium (SCB), and (iii) swab in a gassed-out tube (SGT). Transport tubes were held at 25 degrees C and semiquantitatively sampled at 0, 2, 24, and 48 h. Twenty-five clinical specimens yielded 75 anaerobic strains and 43 isolates of facultative and 3 of ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…showed low resistance to moxifloxacin ( 10 ), while one prospective study described that S. viridans and K. pneumoniae displayed intermediate susceptibility and high resistance to this antimicrobial, respectively ( 27 ). As has been described, methodological and geographical differences in research evaluating bacterial resistance may support these results ( 7 , 38 ).…”
Section: Discussionmentioning
confidence: 67%
“…showed low resistance to moxifloxacin ( 10 ), while one prospective study described that S. viridans and K. pneumoniae displayed intermediate susceptibility and high resistance to this antimicrobial, respectively ( 27 ). As has been described, methodological and geographical differences in research evaluating bacterial resistance may support these results ( 7 , 38 ).…”
Section: Discussionmentioning
confidence: 67%
“…11,21,30 Swab cultures and sonication uid are considered susceptible to various problems, including contamination risk, low specimen volume for culture, and inhibition of pathogen growth. 31,32 Previous studies have reported limited performance of swab cultures compared to tissue cultures for diagnosing orthopaedic implant-related infections. 33,34 Considering that contamination can signi cantly reduce the speci city of detection, we chose tissue sampling for culture and PCR instead of swab or sonication uid.…”
Section: Discussionmentioning
confidence: 99%